Fate or fault? Nurses' perspectives on dementia prevention in German care facilities - Niklas Petersen (Elsevier, 2024)
Following the recent shift in medicine towards viewing dementia as a preventable disease, various activating interventions are being discussed to halt cognitive decline of people living in long-term care facilities. This article examines how the dementia discourse, with its turn towards prevention, translates into local everyday care practices. Based on problem-centered interviews, the study analyses how nurses negotiate the prevention paradigm in the context of current health policies, active aging culture, and institutional frameworks in German nursing homes.The study reveals two contrasting patterns in how nurses perceive, interpret, and implement current principles of dementia prevention in care: Despite most nurses being aware of current prevention recommendations, subjective conceptions of both the impact of lifestyle choices in earlier life and the effectiveness of activating interventions in care settings vary greatly. Adopting conceptions of successful aging, neuroplasticity and activity theory, some nurses understand dementia as associated with earlier lifestyle choices and see prevention as a task of nursing care. Focusing strongly on the individuals' personal needs and the well-being of those in need of care, the other group still sees dementia as fated, suggesting either a critical stance or a more holistic understanding of dementia prevention.Furthermore, institutional frameworks and economization processes in the German care system undermine the goal of strengthening prevention and health promotion. While prevention is promoted as an answer to the care crisis in health policy discourses, the implementation of preventive interventions is severely restricted by the fragmentation of nursing tasks, time constraints, and limited resources in care facilities.